Intelektual Muslim Baru dan Kajian Islam - Azra, Azyumardi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2012)
Book Review: Carool Kersten, Cosmopolitans and Heretics: New Muslim Intellectuals and the Study of Islam, London: Hurst & Company, 2011, xvi+324 pages.This book is a very important contribution to the study of Islam in Southeast Asia, especially Indonesia, a country with the largest Muslims population in the world. The inclusion of Nucholish Madjid in this work on the intellectual dynamics in the Muslim world has a symbolic significance that cannot be avoided. Until the last two decades, Indonesia and Southeast Asia Islam are not seen by most of the Islamic scholars as integral part of Islam and Muslim world. Islam and Muslim in this area are considered peripheral to Islam and Arabic Muslim entities. In fact, this region is home to the largest part of Muslims in the world with its prominent dynamics. Kersten's decision to include Indonesian Muslim intellectual, Nurcholish Madjid, to his work is motivated by his urge to address the imbalance representation on the studies of contemporary Islam and Muslim world.DOI: 10.15408/sdi.v19i1.373